Gonadal guardianship-ergonomic endocrinology - Sanjay Kalra; Bharti Kalra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Reproductive and sexual health is not only an important aspect of human health; it is essential for propagation of the human race. It is imperative, therefore, to focus on prevention of illness as well as promotion of reproductive and sexual health. We term this approach as gonadal guardianship. Keywords: Andrology, endocrinology, gynaecology,